Regulation of the professional relationship: a case study - Tomlinson, Deborah G. (My University, 2011)
The social inclusion of adults with intellectual and developmental disabilities remains an elusive goal for many adults, their families, and allies. Many of the typical relational human interactions people without intellectual and developmental disabilities enjoy and take for granted, have been denied to adults with intellectual and developmental disabilities, largely because of harmful conceptualizations of what it means to live with a disability. These conceptualizations have not only influenced the development of public policy but they have also shaped the interactions and relationships between professionals and adults with intellectual and developmental disabilities. Equipped with the historical knowledge of how public policy was used to cultivate and maintain the mass institutionalization of adults living with intellectual and developmental disabilities – and then subsequently used to lead to it’s demise – this study set out investigate if and how public policy might influence the nature of professional relationships between service users with intellectual and developmental disabilities and service providers. Using qualitative methods guided by critical disability theory, this study looked specifically at how Ontario Regulation 299/10 has already, and/or may in the future, change the interpersonal relationships that exist between adults living with intellectual and developmental disabilities and their care-givers at L’Arche Hamilton. Research methods included working with the policy document and also conducting face-to-face interviews with adults with intellectual and developmental disabilities and their caregivers. It was important for this study to include the voices of adults with intellectual and developmental disabilities and to examine the research question from their perspective because without their input it would not be possible to really understand the regulation’s impact.
This study focused on the current experiences of three residents (core members) and three care-givers (assistants) at L’Arche. It was found that there exist genuine and caring relationships between the two; relationships shaped by the understanding of the assistants that adults with intellectual and developmental disabilities have something of value – a “gift” – to contribute to what they define as a mutual relationship. In addition, both core members and assistants point to the importance of human touch in care-giving interactions – touch that moves beyond the functional (e.g., assistance with personal care) to also include expressive touch (e.g., hugs) that conveys affection and love. However, the findings further suggest that Ontario Regulation 299/10 threatens the ability of care-givers to engage in the intentional form of relationship which currently exists within the L’Arche service model. This form of relationship is understood to be restricted by the regulation under the guise of “protection” and as being “best practice”. The legislation recognizes that people living with disabilities have higher rates of abuse then those living without disabilities; in response to this reality the legislation attempts to reduce opportunity for such abuses to occur and, as a result, articulates clear boundaries around the type of relationships that are permissible. The assistants interviewed for this study also recognize these concerns but they also worry that these concerns overlook the reality of the limited opportunities for genuine relationships between adults with intellectual and developmental disabilities and those without. Further research, directed by adults with intellectual and developmental disabilities, is needed to unpack how this relationship is understood and experienced by both parties, and how each feels it should be maintained, especially in regards to the use of physical touch as an expression of relationship. Research which engages the core members in dialogue on what “safety” and “relationship” mean and looks like for them is needed in order to truly understand the potential impact limiting the professional relationship may have.
Keywords: Social Work; public policy; critical disability theory; L’Arche; professional relationship; Social Work; Social Work